THE INFLUENCE OF SOCIAL ATTITUDES TOWARD THE MAIN CHARACTER DARIUS AS REFLECTED RICHARD OH’S HEART OF THE NIGHT: A SOCIOLOGICAL APPROACH - Catur Kurniawan (LP4MK STKIP PGRI Lubuklinggau, 2011)
The problem of this study were “what is the character of Darius in the novel Heart of the Night? And how is the influence of social attitude toward the main character Darius as reflected in Richard OH’s Heart of the Night?” Therefore, the objective of this study were to describe the characteristics of the main character “Darius”in the novel Heart of the Night, and to find out the influence of social attitude toward the main character Darius as reflected in Richard OH’s Heart of the Night. The writer used descriptive qualitative in this research. In analyzing the data, sociological approach was used to analyze the influence of social attitudes toward the main character “Darius”. The instrument of this research was the researcher herself as thehuman instrument. The writer found out the influence of social attitudes toward the main character “Darius”. The main character Darius get negative and positive influence of social attitudes. The influence negative of social attitudes toward Darius was arrogant, strange of behavior, drinks the alcohol, and temperamental. And in positive influence of social attitudes toward Darius namely tried to move on, care, and he was a best friend.